2021
DOI: 10.1371/journal.pone.0256105
|View full text |Cite
|
Sign up to set email alerts
|

Keel bone fractures in Danish laying hens: Prevalence and risk factors

Abstract: Keel bone fractures (KBF) in commercial poultry production systems are a major welfare problem with possible economic consequences for the poultry industry. Recent investigations suggest that the overall situation may be worsening. Depending on the housing system, fracture prevalences exceeding 80% have been reported from different countries. No specific causes have yet been identified and this has consequently hampered risk factor identification. The objective of the current study was to investigate the preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
31
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 60 publications
6
31
2
Order By: Relevance
“…This finding indicates that the occurrence of KBFs may be associated with the changes in the body weight of laying hens. Moreover, previous studies found that the bodyweight of laying hens affected the keel bone quality and vice versa [ 25 , 26 ], and the laying hens with fractured keel bone generally had a lighter bodyweight than those with a normal keel bone [ 6 , 18 ]. This finding was similar to our observation that the bodyweight of FK laying hens was lower than NK hens and reflects that the bodyweight is related to KBFs in laying hens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding indicates that the occurrence of KBFs may be associated with the changes in the body weight of laying hens. Moreover, previous studies found that the bodyweight of laying hens affected the keel bone quality and vice versa [ 25 , 26 ], and the laying hens with fractured keel bone generally had a lighter bodyweight than those with a normal keel bone [ 6 , 18 ]. This finding was similar to our observation that the bodyweight of FK laying hens was lower than NK hens and reflects that the bodyweight is related to KBFs in laying hens.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, although the current study suggested that keel bone damage could be associated with abnormal bone metabolism reflected by changed serum markers in relation to bone turnover in laying hens, this study had limitations, such as the younger hens, a shorter experimental period, a smaller sample size, and the lack of the analysis of bone mineralization markers and serum RANKL level, as well as the age at onset of lay and the egg production of laying hens in each group. Previous studies reported that these factors could affect the development of KBFs in laying hens [ 26 , 45 ]. Besides, one of the most important limitations is the young age of the laying hens.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent studies on keel bone fractures suggest that especially the fractures located at the caudal tip occur as a result of internal forces ( Thøfner et al, 2020 ). Hens with smaller bodies, an earlier onset of lay, larger egg size at onset of lay are thought to be at an increased risk of developing fractures in the caudal tip of the keel bone ( Thøfner et al, 2021 ). In our study, DW hens had an earlier onset of lay and smaller body size and experienced a greater number of fractures of the cranial section of the keel bone over the course of the study.…”
Section: Discussionmentioning
confidence: 99%
“… Gebhardt-Henrich and Fröhlich (2015) found that the younger hens were when laying their first egg, the higher was the probability of having a keel bone fracture at depopulation. A possible explanation for this finding is the late ossification of the keel bone at about 35 wk of age ( Buckner et al, 1949 ; Thøfner et al, 2021 ). At this age, hens have already been laying eggs for several weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Keel bone damages, that is, fractures and deviations, can be found in all housing systems for laying hens. The overall prevalence in cage systems, single and multi-tier systems, and systems with access to free-range ranged between 3% and 100% of hens within one flock ( Donaldson et al, 2012 ; Petrik et al, 2015 ; Hardin et al, 2019 ; Jung et al, 2019 ; Thøfner et al, 2021 ). The presence of keel bone damage, especially fractures, can cause pain in laying hens ( Nasr et al, 2012 ), which can negatively affect hens’ mobility ( Rentsch et al, 2019 ) and welfare ( Dawkins, 2004 ; Riber et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%